FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM PERCEPATAN PENANGGULANGAN KEMISKINAN DI KOTA BATU - Birgitta Dwi Hardhinawati, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
The purposes of this research are : first, describing communication, resources, disposition, bureaucracy structure, and content of the plan factors in implementing the plan of Poverty Response Accelerating Program in the Town of Batu; second, describing the implementation of Poverty Response Accelerating Program in the Town of Batu; third, analyzing how far the factors of communication, resources, disposition, bureaucracy structure, and content of the plan are collectively related towards the implementation of Poverty Response Accelerating Program in the Town of Batu; fourth, analyzing how far the factors of communication, resources, disposition, bureaucracy structure, and content of the plan are partially related towards the implementation of Poverty Response Accelerating Program in the Town of Batu. Research method used is quantitative approach with explanatory research type. The respondents are the Coordinating Team for Poverty Response of the Town of Batu. Data has been analyzed by using double linear regression model. Based on the test result of double linear regression, it is concluded that the factors of communication, resources, disposition, bureaucracy structure, and content of the plan are collectively influencing the implementation of Poverty Response Accelerating Program in the Town of Batu with adjusted F value of 55,6%. Other than that, the factors of communication, resources, disposition, bureaucracy structure, and content of the plan are partially influencing the implementation of Poverty Response Accelerating Program in the Town of Batu. The correlations shown by Î² of each of variables are communication is 0,395; resources is 0,377; disposition is 0,251; bureaucracy structure is 0,254; and content of the plan is0,278 . It can be concluded that the communication factor is the most dominant factor in influencing the implementation of Poverty Response Accelerating Program in the Town of Batu.